Forty years of change in Scottish grassland vegetation: Increased richness, decreased diversity and increased dominance. (August 2017) - Mitchell, Ruth J.; Hewison, Richard L.; Britton, Andrea J.; Brooker, Rob W.; Cummins, Roger P.; Fielding, Debbie A.; Fisher, Julia M.; Gilbert, Diana J.; Hester, Alison J.; Hurskainen, Sonja; Pakeman, Robin J.; Potts, Jacqueline M.; et al.
Abstract: Assessing effectiveness of international biodiversity targets requires long-term monitoring of species to identify changes in their abundance. Grasslands cover large areas of many countries, provide high levels of provisioning ecosystem services and are an important habitat for many species. While grasslands are often anthropogenic in nature, human-induced environmental perturbations are acknowledged threats to their biodiversity and functioning. Using a repeat survey of grassland plots in Scotland, UK we identified long-term changes in community composition and species indices over a 40 year period (1973–2013). Scottish grasslands were found to have changed significantly over this time. Species richness increased, while diversity declined as dominant species increased in cover. Nitrogen-demanding and moisture-requiring species increased, possibly reflecting increases in atmospheric nitrogen deposition and rainfall over this time. In Acid and Nardus grasslands species with low tolerance to very acidic soils increased, possibly reflecting a decrease in sulphur deposition. Overall β-diversity showed no change, indicating that contrary to trends in other habitats, homogenisation has not occurred. In general bryophytes and low-growing forb and grass species declined while taller species increased. This may reflect either the decline in grazing in recent years or the increase in atmospheric nitrogen deposition. Species richness increased but the majority of species declined in cover while a few dominant species increased suggesting that an extinction debt may be establishing. The trade-offs between increased management to reduce the extinction debt and abandonment with increased shrub cover which might be beneficial to other wildlife is discussed. Highlights: Long term data revealed changes in composition of Scottish grasslands over 40 years. Species richness increased, diversity declined and dominant species increased. Tall species and species with high Ellenberg fertility or moisture scores increased. Bryophytes, forbs and low-growing grass species declined. An extinction debt is suggested to be occurring in Scottish grasslands.